Vigorous and moderate physical activity among overweight and obese adults in Malaysia: Sociodemographic correlates - Cheah, Yong Kang; Mohd, Azahadi; Phang, Siew Nooi; Abd. Manaf, Noor Hazilah (Elsevier Ltd., 2019)
Background This study examines the effects of sociodemographic factors on participation in vigorous and moderate physical activity and how they vary across bodyweight group (underweight, normal, overweight, obese I, obese II).